ReCaLS-in-DLT: resilient consensus algorithm for leader selection in distributed ledger technology - Hussain, Munir; Mehmood, Amjad; Khan, Muhammad Altaf; Wang, Huihui; Song, Houbing Herbert; Maple, Carsten (Cluster computing, 2025)
Distributed ledger technology (DLT) is most widely used in many areas for example healthcare, finance, public welfare, and Internet of Things (IoT) to provide security and effi- ciency. The consensus algorithm is a key component of DLT-based networks that plays a vital role in maintaining the performance of the network and ensuring security. We proposed a consensus algorithm that selects a leader or miner node based on a lucky number for block mining. The proposed algorithm is not only scalable but also enhances security during the consensus process in the presence of less trustworthy nodes, the selected miner node is re-authenticated by the trusted authority before adding a block in the ledger. Apart from the re-authentication process, the trust level of the miner node is also checked. Statistical analysis is performed to prove the security of the proposed algorithm. The results demonstrate that our proposed algorithm offers a good level of resistance against abnormal behavior of the network nodes. Furthermore, performance evaluation is also performed through the Hyper-ledger Fabric Blockchain platform. The simulation results show that the proposed consensus algorithm provides high throughput, low latency, low CPU utilization, and communication bandwidth consumption as compared to the state- of-the-art benchmark proposed in the literature. The lightweight and secure nature of the proposed algorithm makes it a suitable solution for the consensus process in DLT.